Optimizing Pipeline Bridge Components Through FEA Technical Validation - Maria Tănase; Alexandra Ileana Portoacă; Ecaterina Daniela Zeca; Loredana Maria Păunescu (Buildings)
Pipeline bridges are structures characterized by their triangular truss designs, which provide support and stability for pipelines. They have been used for centuries to span gaps and are still widely employed today in various forms and applications. This paper aims to explore the technical and economic aspects associated with optimizing the performance of a pipeline bridge by modifying the constitutive elements. It was investigated how variations in geometric elements and other design characteristics can influence the stress state and the associated material costs, so as to find solutions and strategies that allow the obtaining of a more efficient, safer, and more economical structure, without compromising quality or safety. Different construction scenarios were analyzed, revealing a stress increase of up to 54.77% in comparison to the lowest stress scenario (Scenario 6). Lower stress values were achieved using thicker pipes, with minimal influence from angle dimensions. A statistical analysis using ANOVA, performed in Minitab, showed that both maximum stress and material costs are predominantly influenced by pipe type (99.7% and 81.72%, respectively), rather than angle size. The optimal solution for minimizing stress and costs was determined to be the combination of angle C1 (30 × 30 × 3 mm) and pipe T3 (60.3 × 3.6 mm). This work contributes to the state of practices by providing detailed guidelines on selecting structural configurations that balance cost and performance, making it highly relevant for the design and optimization of pipeline bridges.